Revolutionary Lawyering: Addressing the Root Causes of Poverty and Wealth - William P. Quigley (Washington University Journal of Law & Policy, 2006)
It is true that lawyers are rarely revolutionaries. In fact, the idea may seem like an oxymoron (like corporate ethics), but some people are, and others can be, revolutionary lawyers. Our profession is, at the core of its practice, the primary profession world-wide that protects and defends the machines, computers, profit motives and property rights so rightly condemned by Dr. King. We use our training, wealth, and position in society to facilitate commerce without conscience, to accumulate wealth without responsibility, and to serve the needs of corporations over and above the rights and needs of people. Yet still, some lawyers can be revolutionaries. Part I of this Article highlights some of the most glaring details about poverty, wealth and the working poor and provides some facts about racism, materialism and militarism, both nationally and internationally. The briefest look at who is rich and who is poor, and the reasons behind such status, demonstrates the continued accuracy of Dr. King’s prophetic description of why a radical revolution of values is needed, now even more than when he first spoke these words. Part II of this Article discusses some areas of the law that need radical change, law that needs to be torn up by its roots and replaced. Part III reflects on how lawyers who want to be revolutionaries can do so. The Article concludes with signs of hope and a charge to lawyers to consider joining the radical revolution of Dr. King.
Keywords: Poverty; Revolutionaries; Social change; Social justice; Race discrimination; Militarism; Materialism; Wealth; United States; Racism